A geologia do Maciço Santa Angélica e suas encaixantes (Espírito Santo) - Marcela Lopes Zanon (2013)
The Santa Angelica Massif (CISA), located in the southern Espírito Santo state, is the G5 suite more important pluton (Araçuaí Orogen post-collisional stage), and is constituted by leucocratic and melanocratic rocks in a magma mingling zone. This pluton intruded the rocks of G1 suite (Araçuaí Orogen pre-collisional stage) and the Paraiba do Sul Complex. The processes of physical and chemical dynamic of mafic and felsic magmatism of the CISA and the gneiss margin (G1 suit) is studied herein, considering the structural features. In order to do this, fieldwork, petrographic microscopic study, microprobe analysis and geochemicalanalyses were realized. The interpretation of this data resulted in the model tectono-magmatic in which are discussed the two main deformation phases associated the G1 suites rocks and how they influenced the process of intrusion and shaping the CISA from regional shear zones. Were also shown the parcial melting process the gneiss margin (G1 suite) (genesis the G5s syenogranite and syenogranite more young) as well as the magmatic differentiation process (fractional crystallization) involving the two gabbroics nucleus of the G5 suite (genesis of other CISAs rocks) and the most important aspects of the magma mingling zone.